Jordan : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director, and Advisor for Jordan. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Jordan's Request for Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 pandemic has had a severe impact on the Jordanian people's lives and on the economy. Tourism disruption and sharp declines in remittances, exports and capital inflows have resulted in an urgent balance of payments need. The Jordanian authorities have responded with decisive containment and health measures that effectively limited the spread of the virus with minimal fatalities. They also implemented a timely package of policies to mitigate the economic fallout of the pandemic. IMF financing under the RFI will support international reserves and help meet the budget financing needs for crisis mitigation. Mobilizing additional financing from multilateral and bilateral creditors will be essential to support the authorities' policy efforts and preserve macroeconomic stability. The authorities remain committed to the objectives of the reform program supported by the Extended Fund Facility arrangement, which was approved by the Board in March. When the crisis abates, the priority will be resuming fiscal consolidation to place public debt on a declining path and pursuing reforms to strengthen the competitiveness of the Jordanian economy and to support inclusive growth and job creation.